Risiko Ergonomi dan Keluhan Musculoskeletal Disorders (MSDs) pada Pengrajin Tenun di Palembang - Tiara Putri Yosineba; Erial Bahar; Msy Rulan Adnindya (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Ergonomic Risk and Musculoskeletal Disorders (MSDs) among Weavers in Palembang. Musculoskeletal disorders (MSDs) are disorders characterized by injuries in the muscles, ligaments, nerves, joints, cartilages, bones, or blood vessels. One of the many risk factors for MSDs is work posture. Weaving craftsmen are threatened with MSDs symptoms because they have a risky work posture, which is a static sitting position for a long time and various awkward postures such as turning, bending and reaching. This study aimed to determine the correlation of ergonomic risk and symptoms of MSDs among weavers in Palembang. The study was an analytic observational with cross-sectional design. The sample of this study was weavers in Palembang, which were 35 workers. The symptoms of MSDs were assessed by an interview based on the Nordic Body Map (NBM) questionnaire whereas ergonomic risks were assessed by using Rapid Upper Limb Assesment (RULA) worksheet. The data collected were analyzed using Spearman correlation analysis. The results showed that in the process of producing weaving there were two categories of work posture, those were high-risk work posture (88.6%) and very high-risk work posture (11.4%). The results also showed that the most common symptoms of MSDs were located in the upper neck (67.5%), lower neck (57.1%), waist (54.1%) and hip (42.9%). The result of Spearman correlation analysis showed that there was a significant moderate correlation (r=0.573 ; p =0.000) between ergonomic risk and symptoms of MSDs.